IMPLEMENTASI BLOCKCHAIN DALAM TRANSFORMASI LEMBAGA KEUANGAN SYARIAH MELALUI SMART CONTRACT PRODUK PERBANKAN - Makki, Mustaqim; Susanto, Andi; Roifah, Tri Nadhirohtur (STAI Nurul Huda Kapongan Situbondo, 2024)
Introduction: This article discusses the implementation of Blockchain in Islamic financial institutions through smart contract banking products, focusing on data security and transparency. The library research method is used to analyze the implementation of Blockchain in Islamic financial institutions. Secondary data from literature is utilized to support arguments and conclusions. Blockchain technology enables the formation of interconnected blocks storing verified and encrypted transaction information, with a consensus system reducing the risk of data manipulation. Smart contracts can automate the process of borrowing and returning library materials, enhancing operational efficiency and data security. The application of Shariah-compliant Smart Contracts in Islamic banking can facilitate fair, transparent transactions in line with Shariah principles, minimize the risk of Shariah violations, and increase public trust. Implementing Shariah-compliant Smart Contracts in Islamic financial institutions through Blockchain technology requires consultation with Shariah legal experts and authorities to ensure compliance with Shariah principles and relevant Shariah financial regulations, strengthening the Islamic financial ecosystem. Keyword: Blockchain, Islamic financial institutions, smart contracts,